Penerapan Teknologi Closed system Pada Pembudidaya Udang Vaname (Litopenaeus vannamei) Kelompok “Laut Mina Budidaya” Bireuen, Aceh - Yusrizal Akmal; Rindhira Humairani; Mandasari; Ilham Zulfahmi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
Lipah Rayeuk Village located on the Bireuen Regency which has potential marine and brackish fishery resources, especially vannamei shrimp ponds, but the problem in vannamei shrimp ponds was lack of understanding of water quality management, open system still used as water management system for the pond, technology and management of shrimp farming aren’t yet understood, causing the production of each harvest to decrease. This service aims to apply appropriate technology in form if closed system and probitic applications in water to meet quality standards in the pond water management system. The community service program is carried out in the Mina Budidaya Laut group in Lipah Rayeuk Village, Bireuen Regency. The method used in this activity is assisting the improvement of cultivation technology which applied is closed system and the application of probiotics to water. Increased understanding of partners about knowledge and practical closed system applications from 3.53% to 10.91%. Increasing the knowledge and ability of partners in water quality management and closed system applications in vannamei shrimp cultivation, partners can run biosecurity so that in the end there will be an increase in production and quality of the shrimp produced which can increase the selling value of vaname shrimp.